The Influence of Entrepreneurship Literacy and Digital Literacy on Entrepreneurial Interest among Generation Z Students - Febriani, Fitri Indah; Swaramarinda, Darma Rika; Maulida, Ervina (Klabat Journal of Management, 2025)
This study aims to examine the influence of entrepreneurship literacy and digital literacy on the entrepreneurial interest of Generation Z students. A quantitative research design was employed using a survey method. The target population comprised 1,950 undergraduate students from the Faculty of Economics and Business at Jakarta State University, enrolled in the 2021–2022 academic year. The sampling technique combined purposive sampling with proportionate stratified random sampling. Using the Isaac and Michael formula with a 5% margin of error, a sample of 321 students was selected. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach, implemented through SmartPLS 4.0 software. The data analysis procedure included measurement model evaluation, structural model assessment, and hypothesis testing of direct effects. The results of the study revealed the following: (1) entrepreneurship literacy has a positive and significant influence on entrepreneurial interest; (2) digital literacy also has a positive and significant influence on entrepreneurial interest; and (3) both entrepreneurship literacy and digital literacy jointly exert a positive and significant influence on the entrepreneurial interest of Generation Z students from the Faculty of Economics and Business, Jakarta State University, class of 2021–2022.